Environmental externality cost of tofu agroindustry center in Gadingrejo Village, Pring Sewu Regency - Rafiq, Muhamad; Abidin, Zainal; Suryani, Ani (Agriekonomika, 2024)
This research analyze environmental externality costs by estimate the value of Willingness to Pay (WTP), Willingness to Accept (WTA), and the effect of environmental costs on the profits of the Tofu Agroindustry in Gadingrejo Village Pringsewu Regency. This research method is a case study. Respondents were determined purposively with a total of 12 agro-industries and 48 communities. Research data were collected from October to November 2023. The analytical method used was Contingent Valuation Method (CVM) to estimate WTP and WTA values and profit analysis to see the difference in profits before and after internalizing environmental costs. The results showed that the average WTP value was Rp94,791 per month per agro-industry. The average WTA value was obtained at Rp26,875 per month per community. There was a decrease in the average profit of agro-industry by 1.12% per month or Rp94,791.67 after internalizing environmental costs.